2009
DOI: 10.1007/s11255-009-9526-0
|View full text |Cite
|
Sign up to set email alerts
|

Relation of stiffness parameter β to carotid arteriosclerosis and silent cerebral infarction in patients on chronic hemodialysis

Abstract: These results suggest that arteriosclerosis assessed by stiffness parameter beta is associated with atherosclerotic changes of carotid arteries and with the presence of SCI in HD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 33 publications
1
21
0
1
Order By: Relevance
“…The mean IMT was also significantly correlated with those variables except for BMI. Although there was a significant positive correlation between the stiffness parameter b and the mean IMT, the correlation was not strong (r = 0.33, P \ 0.0001), which is consistent with a previous report [21]. These results indicate that different mechanisms might contribute to arterial stiffness and thickness.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The mean IMT was also significantly correlated with those variables except for BMI. Although there was a significant positive correlation between the stiffness parameter b and the mean IMT, the correlation was not strong (r = 0.33, P \ 0.0001), which is consistent with a previous report [21]. These results indicate that different mechanisms might contribute to arterial stiffness and thickness.…”
Section: Discussionsupporting
confidence: 86%
“…A parameter for assessing arterial wall stiffness, the stiffness parameter b, has been developed and has been reported to be independent of blood pressure [16]. It has been used to evaluate arterial stiffness in patients with type 2 diabetes [17][18][19] and in patients with chronic renal disease [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…All subjects underwent a brain MRI (EXCELART, Toshiba Co., Tokyo, Japan) with a superconducting magnet at a field strength of 1.5 T on proton density, T1-, and T2-weighted images were acquired in the axial planes at 10 minutes thick slices as previously described (12). Infarction was diagnosed when a focal area larger than 3 mm in diameter was observed on both T1-and T2-weighted images and was visible as a low-signal intensity area on the T1-weighted image and as a high-signal intensity area on the T2-weighted image.…”
Section: Diagnosis Of Scimentioning
confidence: 99%
“…They concluded that recognition of this characteristic as an important predictor of mortality suggests that one goal of antihypertensive therapy in patients with PD should be to decrease elevated pulse pressure. Moreover, Ogawa et al [48] showed that arteriosclerosis assessed by stiffness parameter beta is associated with atherosclerotic changes of carotid arteries and with the presence of silent cerebral infarction in patients with HD . Haydar et al [49] found that PWV strongly correlates with total calcification scores assessed by means of EBCT, even after correction for age, dialysis therapy duration, prescribed dose of calcium-containing phosphate binders, and microinflammatory status.…”
Section: Pathogenesis Of Arterial Stiffnessmentioning
confidence: 99%